The genus Acropimpla Townes (Hymenoptera: Ichneumonidae: Pimplinae) in Vietnam, with descriptions of three new species - Pham, Nhi Thi; Broad, Gavin R.; Wägele, Wolfgang J. (Zootaxa, 2011)
Six species of Acropimpla Townes, 1960 are recorded from Vietnam, of which three species are described as new: A. lampei sp. nov. from Ea So, Dak Lak Province, Central Highlands of Vietnam, A. mucronis sp. nov. from Cat Tien, Dong Nai Province, South Vietnam, and A. phongdienensis sp. nov. from Phong Dien, Thua Thuen-Hue Province, Central Vietnam. Two species, A. hapaliae (Rao, 1953) and A. taishunensis Liu, He & Chen, 2010 are recorded from Vietnam for the first time.